2021
DOI: 10.1101/2021.12.08.471811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ion Permeation, Selectivity, and Electronic Polarization in Fluoride Channels

Abstract: Fluoride channels (Fluc) export toxic F- from the cytoplasm. Crystallography and mutagenesis have identified several conserved residues crucial for fluoride transport, but the transport mechanism at the molecular level has remained elusive. Herein we have applied constant-pH molecular dynamics and free energy sampling methods to investigate fluoride transfer through a Fluc protein from Escherichia coli. We find that fluoride is facile to transfer in its charged form, i.e., F-, by traversing through a non-bonde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 123 publications
(220 reference statements)
1
3
0
Order By: Relevance
“…The PMFs calculated here result in energy barriers of 0.1-2.6 kcal/mol, which is comparable to the PMFs previously reported for the CLC Cl -/H + antiporter which gave energy barriers of between 2 and 4 kcal/mol. 42,43 Additionally, we have shown that CLC F is transporting fluoride as an anion and not as HF, as the latter creates very large energy barriers for the system to overcome, a result which complements the recent work by Yue et al 36 on the Fluc Fchannel. This work is among the first reported computational studies of the CLC F antiporter protein, and is the first to propose a mechanism to couple the proton import with Fexport.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The PMFs calculated here result in energy barriers of 0.1-2.6 kcal/mol, which is comparable to the PMFs previously reported for the CLC Cl -/H + antiporter which gave energy barriers of between 2 and 4 kcal/mol. 42,43 Additionally, we have shown that CLC F is transporting fluoride as an anion and not as HF, as the latter creates very large energy barriers for the system to overcome, a result which complements the recent work by Yue et al 36 on the Fluc Fchannel. This work is among the first reported computational studies of the CLC F antiporter protein, and is the first to propose a mechanism to couple the proton import with Fexport.…”
Section: Discussionsupporting
confidence: 84%
“…42,43 Additionally, we have shown that CLC F is transporting fluoride as an anion and not as HF, as the latter creates very large energy barriers for the system to overcome, a result which complements the recent work by Yue et al . 36 on the Fluc F - channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29-38. But computational studies of anion transport mechanisms demonstrated by chloride-selective channels [39][40][41][42] that address comparison to alternatives such as FLUC are less mature. 3,43 A conceptually natural strategy to address ion selectivity with computation would be direct simulations controlling for the contrasting cases, or perhaps a clear, quantitative theory that permits controlling for mechanistic features of the ion binding or transport. Both of these requests are difficult.…”
Section: Context: Selectivity Of Membrane Ion Channelsmentioning
confidence: 99%